Analisis Faktor-Faktor Penentu Keputusan Orang Tua dalam Memilih Sekolah Berbasis Pesantren - Salsabilah, Balqist Naurah; Riza, Fahrul; Sarwoko, Endi (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
School selection by parents is an important decision influenced by internal and external factors, such as location, cost, curriculum, facilities, and school reputation. This study aims to identify the main factors affecting parents’ decisions in choosing Islamic-based elementary schools. The theoretical foundation is based on consumer behavior and decision-making theories, which explain how individuals make choices based on perceived value, needs, and available information. The research employed a quantitative approach using surveys, analyzed descriptively and inferentially. The results indicate that the quality and religious values of the school are the dominant factors, including parental religiosity, quality of religious education, teacher competence, value-based curriculum, student achievement, and the development of students’ character and spirituality. Schools are recommended to focus on improving religious education, strengthening character, enhancing teacher competence, implementing a professional curriculum, and building reputation through the publication of achievements, testimonials, and creative promotional strategies. Transparency in facilities and costs is also essential to foster a positive image and increase parental trust. This study has several limitations, including the use of subjective survey data, a limited number of respondents, and a focus on Islamic junior high schools in East Java, which restricts the generalizability of the findings to other schools or regions.